Pengembangan Media Pop Up Book Berbasis Permainan Pada Pembelajaran Tematik di Sekolah Dasar - Febriani Febriani (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
This research aims to describe the stages, feasibility, and student responses to game-based pop up book media in thematic learning in elementary schools. This study uses the research and development (R&D) method by Borg and Gall in Sukmadinata (2010: 169-170) which occurs from several stages as follows: (1) Conducting preliminary studies (2) Product planning (3) Product draft development (4 ) Individual trials (5) Revising the results of field trials (6) Limited trials, (7) Improvement of products resulting from limited trials (8) Extensive implementation tests (9) Completion of the final product. Data collection techniques were carried out using interview techniques, questionnaires and documentation. The research was conducted with 4 stages of validation, namely material expert validation, media expert validation, linguistic expert validation and student response questionnaires. The results showed that the validity level of material experts reached a percentage of 88% which was included in the "Very Eligible" category, the media expert's validity level reached a percentage of 90.83% which was included in the "Very Eligible" category, and the validity level of linguists reached a percentage of 87.49% who entered in the "Very Eligible" category, and the student response questionnaire reached a percentage of 97.20% which was included in the "Very Good" category. So it can be concluded that the game-based pop up book media in thematic learning in elementary schools is feasible to be used in thematic learning.Penelitian ini bertujuan untuk mendeskripsikan tahapan, kelayakan, dan respon siswa terhadap media pop up book berbasis permainan pada pembelajaran tematik di Sekolah Dasar. Penelitian ini menggunakan metode penelitian dan pengembangan (R&D) oleh Borg dan Gall dalam Sukmadinata (2010: 169-170) yang terjadi dari beberapa tahapan sebagai berikut: (1) Melakukan studi pendahuluan (2) Perencanaan produk (3) Pengembangan draf produk (4) Uji coba perorangan (5) Merevisi hasil uji coba lapangan (6) Uji coba terbatas, (7) Penyempurnaan produk hasil uji coba terbatas (8) Uji pelaksanaan secara luas (9) Penyempurnaan produk akhir. Teknik pengumpulan data dilakukan menggunakan teknik wawancara, angket dan dokumentasi. Penelitian dilakukan dengan 4 tahap Validasi yaitu validasi ahli materi, validasi ahli media, validasi ahli bahasa dan angket respon siswa. Hasil penelitian menunjukan bahwa tingkat validitas ahli materi mencapai presentase 88% yang masuk dalam kategori “Sangat Layak”, tingkat validitas ahli media dari mencapai presentase 90.83% yang masuk dalam kategori “Sangat Layak”, dan tingkat validitas ahli bahasa mencapai presentase 87.49% yang masuk dalam kategori “Sangat Layak”, serta angket respon siswa mencapai presentase 97.20% yang masuk dalam kategori “Sangat Baik”. Sehingga dapat disimpulkan bahwa media pop up book berbasis permainan pada pembelajaran tematik di sekolah dasar layak untuk digunakan dalam pembelajaran tematik.